Pengaruh Pembelajaran Pendidikan Agama Kristen Dan Budi Pekerti Terhadap Pembentukan Sikap Spiritualitas Siswa Kelas VIII SMP Negeri 1 Simanindo Tahun Pembelajaran 2022/2023 - Renauli Simajuntak; Dorlan Naibaho; Pestaria Naibaho (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the influence of Christian Religious Education and Character education on the formation of spiritual attitudes in class VIII students at SMP Negeri 1 Simanindo for the 2022/2023 academic year. The method used in this research is quantitative descriptive inferential. The population is all class VIII students of SMP Negeri 1 Simanindo for the 2022/2023 academic year, totaling 155 people and a sample of 40 people was determined, which is 25% of the total population. Data was collected using a positive closed questionnaire with 36 items. The results of data analysis show that there is an influence of Christian Religious Education and Moral Education learning on the formation of spiritual attitudes of class VIII students at SMP Negeri 1 Simanindo for the 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.536 > rtable (a=0.05,n=40) = 0.312, thus it is known that there is a positive relationship between variable n-2=38)= 2.021, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 28.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=18, dk denominator=n-2=40-2=38) namely 15.35 > 1.51 Thus Ha accepted and H0 rejected.